Regional factors associated with the distribution of South American fur seals along the Atlantic coast of South America - Tunez, Juan Ignacio (2008)
Breeding colonies of the South American fur seal (Arctocephalus australis) are not homogeneously distributed along the coast of the Atlantic Ocean, but show an unusual patchiness, with colonies located only at the northern and southern extremities of the breeding range. We used bibliographic data of censuses carried out in the mid- and late 20th century, along with a Geographic Information System, to compare the pattern of distribution of colonies during these two periods, and to identify the anthropogenic and natural factors associated with the present pattern at a regional scale, using principal components analysis. The distribution of colonies did not vary in the period analysed even when the population abundance increased tenfold. The distribution was associated with the distance to the continental shelf break, and the availability of island and protected areas. We conclude that A. australis colonies are located in places where the continental shelf is narrow and there is no human disturbance.